JOHN SUNG'S MALLEABLE CONVERSION NARRATIVE. - Ireland, Daryl R. (Fides et historia, 2013)
The article focuses on Chinese evangelist Siong Ceh "John" Sung an his experience of converting to Christianity while attending the Union Theological Seminary (UTS) in New York City in 1927. The author analyzes if Sung's spiritual awakening was really the onset of schizophrenia, discusses the political and theological aspects of Sung's revivalism, and explores the history of Chinese Christianity.